FROM MOLECULES TO MASS PROTECTION: THE CONVERGENCE OF BIOTECHNOLOGY AND NANOTECHNOLOGY IN MODERN PUBLIC HEALTH DEFENSE (Journal of Medical & Health Sciences Review, 2026)
Global pandemics have become one of the most significant threats to human health, economic stability, and social order in the twenty-first century. The rapid spread of infectious diseases such as COVID-19, Ebola, Zika, SARS, and influenza has exposed major weaknesses in traditional public health systems, particularly in surveillance, diagnostics, prevention, and response capacity. Factors such as globalization, climate change, urbanization, and increased human–animal interaction have further intensified the frequency and impact of pandemics, making conventional control measures alone insufficient. This  article explores the role of biotechnology and nanotechnology as next-generation defenses in global pandemic preparedness and response. Advances in biotechnology, such as genomic surveillance, molecular diagnostics, mRNA vaccine platforms, monoclonal antibodies, and precision medicine have enabled rapid pathogen identification, accelerated vaccine development, and targeted therapeutic strategies. These innovations allow public health systems to move from reactive outbreak management toward proactive and predictive disease control. In parallel, nanotechnology contributes through highly sensitive nanoscale diagnostics, biosensors, lab-on-a-chip devices, improved vaccine stability, and targeted drug delivery systems, particularly benefiting low-resource and decentralized settings. The article also examines the integration of these technologies into public health infrastructures using digital health platforms, artificial intelligence, and bioinformatics to support real-time data analysis and coordinated decision-making. Ethical, regulatory, and governance challenges including equity, intellectual property, data privacy, biosafety, and biosecurity are critically discussed, emphasizing the need for fair access and global collaboration. Overall, the convergence of biotechnology and nanotechnology offers transformative potential to strengthen health system resilience. When supported by ethical governance, public trust, and international cooperation, these technologies can significantly enhance global preparedness and protection against future pandemics.